Legal Protections for Limited Liability Company Shareholders with Mental Health Disorders - Fakhri M, Rivaldo (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
Minority shareholders, including those suffering from mental illness, frequently encounter numerous obstacles in securing adequate legal protection. The study employs a normative juridical method with a statutory approach to address its objectives. The results showed that the shareholders can file direct lawsuits against the company or derivative lawsuits on behalf of the company if the directors or management engage in unlawful activities that infringe on their rights, as outlined in the corporation law. They can also initiate lawsuits against the company in cases of loss or psychological harm. In situations where the company suffers a loss, the right to sue belongs to the company itself, not to the minority shareholders, reinforcing a bias towards the directors over minority shareholders, including those with mental disorders, since the directors are authorized to represent the company in legal matters.